The Discourse on the Role of NGOs in Indonesia’s Public Policy Process - Bahar, Adam Amin; Mardiyanta, Antun; Mirdad, Mohammad Ayub; Wisnuyana, Biandro (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the discourse surrounding the role of Non-Governmental Organizations (NGOs) in the public policy process in Indonesia. After the collapse of the New Order regime, the role of NGOs has become increasingly prominent in various stages of the policy process, from advocacy, formulation, implementation, to policy monitoring. However, the dominant discourse in Indonesia tends to reduce the political role of NGOs to only two main domains: community development and empowerment and humanitarian assistance. Using a post-structuralist approach and reflective document analysis, this study identifies distinctive characteristics in the discourse on the role of NGOs in Indonesia. Although the role of NGOs in the public policy process is very significant, their political dimensions are often not widely recognized, both by the general public and public policy academics in Indonesia. This condition actually opens up opportunities for NGOs to maneuver more flexibly in institutional and social spaces, influencing policy decisions while maintaining an image of neutrality in the wider political real.